Loading techniques for OFDM systems with nonlinear distortion effects - Araújo, Teresa (2012)
In this paper, we study the impact of nonlinear distortion effects on adaptive orthogonal frequency division multiplexing systems. An analytical statistical characterisation of the transmitted signals, which is obtained by taking advantage of the Gaussian-like nature of the orthogonal frequency division multiplexing signals when the number of subcarriers is high, is included. This statistical characterisation is used to evaluate loading algorithms in the presence of strong nonlinear distortion effects and to redefine loading algorithms taking into account nonlinear distortion issues.